Helena Wayne (red.): The Story ofa Marriage. The Letters of Bronislaw Malinowski and Elsie Masson. - Liep, John (Tidsskriftet Antropologi, 1996)
The Letters of Bronislaw Malinowski and Elsie Masson. 175 Anmeldes af John Liep.